Deformation mechanism of copper reinforced by three-dimensional graphene under torsion and tension. (6th January 2022) - Li, Jinming; Xu, Yixin; Wang, Miaocao; Zhu, Fulong; Hu, Jianxiong; Feng, Chenzefang; Huang, Yuhua; Zhang, Xiang; Zhao, Naiqin; He, Chunnian
Abstract: The mechanical behaviors of uniaxial torsional and tensional copper nanorod embedded with sp 2 -type hybrid graphene nanosheets (3DG/Cu) were investigated systematically using molecular dynamics methods. During the torsion process, graphene expanded the plastic deformation region of copper, while the plastic deformation in monocrystalline Cu cases was limited to a smaller area. 3DG/Cu responded to the torsion by one more plastic stage when plastic deformation spread along the length after the elastic response. Graphene improved the torsional loading capacity of the composite material, greatly extending the effective response range of the material by distributing the deformation of copper along with the graphene rather than being concentrated at a certain position like monocrystalline Cu. Generally, as the length of the model increased, this enhancement decreased. The copper portion of 3DG/Cu was divided into three areas during uniaxial tensile, a static region, a quasi-static region of the middle portion where the shear and necking occurred, and a dynamic area near the loading end. However, the inside graphene kept continuous until fracture. Furthermore, graphene improved the yield strain of copper by maintaining intact after copper failure. The greater the pre-loaded torsion angle, the smaller the yield strength and Young's modulus of 3DG/Cu.